Computed Tomography Imaging of Iatrogenic Esophageal Injuries. Issue 3 (17th May 2022) - Sargent, Tyler; Al-Katib, Sayf
Abstract: Knowledge of iatrogenic esophageal injuries is important given the variety of etiologies, including medical instrumentation (eg, endoscopes), radiotherapy, and anticoagulation. The clinical presentation and imaging findings of esophageal injuries depend on the mechanism and location of the injury. Imaging modalities commonly used for the evaluation of esophageal injuries include esophagram and computed tomography. Esophageal injuries should be considered in patients with acute chest symptoms. Recognizing an unsuspected esophageal injury on imaging can be critical to reaching the correct diagnosis given their nonspecific symptomatology. This review article highlights various iatrogenic esophageal injuries and their appearance on computed tomography imaging.